IMPLEMENTASI KEBIJAKAN PEMBERDAYAAN USAHA KECIL MASYARAKAT DI KECAMATAN TUMINTING KOTA MANADO - ASTONO, MARIYATI; OGOTAN, MARTHA; KIYAI, BURHANUDDIN (Sam Ratulangi University, 2019)
The implementation of small business empowerment policies is one of the implementation ofprograms/activities carried out and managed by the Office of Cooperatives and Small MediumEmpowerments to help small business actors yo develop business run by small business actors.Empowerment of small businesses is an effort to prosper the community with the implementation ofsocialization, programs, and small business trainings in order to prosper the economy of the small businesscomunity. Based on the results of the research carried out by the authors at the Cooperative and SmallMedium Empowerment agency, the program has been in the form of socialization and training on smallbusiness empowerment and several programs have been realized, although not all small business actorshave not participated in the activity due to lack of information about small business empowerment. Thisstudy uses a qualitative approach. The data analyzed is based on the results of interviews with the Office ofCooperatives and SMEs as well as the community of small businesses, observations or direct observationsboth at the Office of Cooperatives and Small Medium Empowerments in Tuminting District, Manado City.By using four indicators, namely Communication, Resources, Disposition, Bureaucratic Structure. Basedon the results of the study it can be concluded that the implementation of small business empowermentpolicies has not been effective, because there are still constraints in the form of limited communicationbetween implementors and small business actors, lack of mastery of science and technology, and lack ofmanagement management, and capital issues. Based on the conclusions the authors suggest that thegovernment pay more attention to existing constraints or problems that occur in the empowerment of smallbusiness communities.Keyword : Implementation, Policy, Empowerment, Small Business